Applying Cross-Spectral Analysis in Research on the Dynamics of the Dax Share Index - Łuczyński, Wiesław (Studia Oeconomica Posnaniensia, 2015)
The squared coherency of independent variables and dynamics of the DAX share index for low frequencies assumes considerably lower values than for high frequencies. The phase spectrum (phase shift) of the DAX share index and unemployment demonstrate the linear and positive relationship for low frequencies (where we observe considerable values for the squared coherency). It would suggest that long term changes in unemployment lead to appropriate changes in the dynamics of DAX share index. However in case of the DAX spectrum and the prices of industrial goods the linear relationship is negative which suggests a lag in changes in prices of industrial goods in relation to changes in the DAX share index. The cross-spectral research carried out shows that in the period analysed the dynamics of a DAX share index are correlated with the dynamics of selected economic processes in different frequencies of the trade cycle. It is then possible to talk about the symptoms of correlated cyclical behaviour. On examining a period of time in the German economy diversified phase spectrums and gains in low as well as in high frequencies of cyclical fluctuations were revealed and deserves special mention. Therefore cross-spectral analysis can be an effective tool supporting the process of the construction of barometers of economic activity and the policy of stabilization or economic recovery.